Principal's Strategy in Completing Educational Facilities and Infrastructure - Linda Dea Atlis; Syafaruddin; Muslim Afandi (Journal of Practice Learning and Educational Development, 2025)
This study aims to examine the principal's strategy in completing educational facilities and infrastructure. This research method uses a qualitative descriptive method obtained through observation data, interviews, and documentation from 5 research informants at Madrasah Aliyah Negeri 4 Kampar. The results show that the principal's strategy in completing facilities and infrastructure is carried out through the stages of facility and infrastructure management, namely planning, procurement, arrangement, use, maintenance, and removal of facilities and infrastructure at Madrasah Aliyah Negeri 4 Kampar. Thus, Madrasah Aliyah Negeri 4 Kampar can be said to have carried out the process of completing educational facilities and infrastructure, and the principal has implemented several strategies in completing educational facilities and infrastructure at Madrasah Aliyah Negeri 4 Kampar. However, in this case, the principal also needs to make improvements to some facilities and infrastructure to make them more complete, adequate, and comfortable.